Relationship Between Toddler Characteristics And Bronchopneumonia Incidence - Sry Rizki; Asmima Yanti; Fitri Apriani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Bronchopneumonia is the leading cause of death in toddlers. The incidence of Bronchopneumonia in Indonesia is 31.4%, in Aceh it is 22.62%. The incidence of Bronchopneumonia in the pediatric ward of Dr. H. Yuliddin Away Tapaktuan Hospital ranks second after diarrhea cases. Toddler characteristic factors that influence the incidence of bronchopneumonia are: age, gender, birth weight, history of breastfeeding, nutritional status, and history of immunization. Research Objective: This study was conducted to determine the relationship between toddler characteristics (gender, birth weight, history of breastfeeding, nutritional status, history of immunization) and the incidence of bronchopneumonia in the pediatric ward of Dr. H. Yuliddin Away Tapaktuan Hospital. Research Method: This study used a descriptive analytical method. While to analyze bivariate data by testing the relationship between independent and dependent variables with the chi-square test. The respondents of the study were parents of toddlers whose children were treated in the pediatric ward of Dr. H. Yuliddin Away Tapaktuan Hospital as many as 50 respondents. Conclusion: Based on the chi-square test analysis, it shows that there is a relationship between several toddler characteristic variables and the incidence of bronchopneumonia at RSU DR. H. Yuliddin Away Tapaktuan, namely low birth weight p value 0.026, non-exclusive breastfeeding p value 0.029 and poor nutritional status p value 0.018. The results of the p value <0.05 so that there is a significant relationship between the independent and dependent variables. Suggestion: The results of this study can be input to the institution of DR. H. Yuliddin Away Tapaktuan General Hospital and become a guideline for improving health services for toddlers with bronchopneumonia.